Implementasi E-Learning Dalam Pembelajaran Pendidikan Agama Islam di SMK Muhammadiyah Sumowono - Hadiyatno Adati; Hafidz Hafidz (Jayapangus Press, 2026)
Educational digitalization demands the precise integration of digital technology, yet its application in Islamic Religious Education (IRE) within vocational schools frequently encounters infrastructural challenges and teacher pedagogical readiness. This study aims to analyze the implementation of e-learning-based digital technology in IRE learning at SMK Muhammadiyah Sumowono, its implications for the instruction, and the supporting and inhibiting factors affecting its execution. A qualitative approach with a case study design was employed, involving two IRE teachers and one Information and Communication Technology (ICT) teacher. Data were gathered through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model. The findings indicate that e-learning implementation utilized Google Classroom, WhatsApp, YouTube, Quranku, and Muslim Pro to support material delivery, communication, evaluation, and practical religious learning. This integration enhanced material accessibility and supported the visualization of abstract concepts in alignment with digital constructivism and the Cognitive Theory of Multimedia Learning. However, its effectiveness remained largely limited to a passive administrative function in classroom management. Supporting factors included the availability of students' devices, supportive school policies, and teacher adaptability. Conversely, inhibiting factors comprised unstable internet bandwidth, variations in teachers' digital literacy, as well as digital distractions and pseudo-engagement among students. In conclusion, while e-learning implementation is adaptive enough to optimize learning, its sustainability requires continuous strengthening of teachers' digital competence, infrastructure upgrades, and the consistent application of blended learning methods.